Examining independent podcasts in Portuguese iTunes - Antunes, Maria João (2020)
The purpose of this paper is to compare and analyse a sample of podcasts, using the most popular podcasts of iTunes (Top 200 podcasts - Portugal). The data was collected in two different dates (October 1st 2018 and October 15th 2019), using a Portuguese Apple ID. Results show that in October 2018 few Portuguese independent podcasts were presented among the top 200 podcasts in iTunes (22 podcasts). The authors/producers were mostly male persons. The podcasts were mainly dedicated to entertainment (comedy), and the contents were characterized by a freedom of expression impossible to include into any commercial or public media. In October 2019 the top 200 podcasts in iTunes (Portugal) presents a higher number of Portuguese independent podcasts (35 podcasts). The podcasts were included in a greater diversity of categories (e.g. entertainment, society, health & well-being, and politics). There is an increasing integration of podcasting with other services and social networks, including website/blogs, Instagram, YouTube, and Facebook. Among the most popular contents it was noticed a greater parity between authors/producers (men versus women).